NEUERE ENTWICKLUNGEN IM DEUTSCHEN GMBH‐KONZERNRECHT - Servatius, Wolfgang (Revista da Faculdade de Direito do Sul de Minas, 2010)
The German law about groups of companies is quite unique in the international company laws. Its genereral scope is to create a close concept on the questeion to what extend it is allowed to make use of corprations for exterior interests. The German company law provides special regulations for groups of companies since 1965. Nevertheless, this specific approach is beeing minimized by recent decisions of the German Federal Court of Civil Law. Especially for Limited Liability Companies the Court shifts the basis of the relevant rules to a general tort law approach. Herafter, shareholders who use a corporation for exterior inetrest are not liable under specific company law rules but by the general rule of tort law. The article demonstrates the development of this legal question and gives critical remarks on it.